The Relationship Between Psychosocial Stressors and Burnout in Football Referees in Bandung City - Ghaly Qori Mubaroq; Nurlan Kusmaedi; Syam Hardwis (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Football referees play a crucial role in maintaining the integrity and smooth running of matches, yet they frequently face social and emotional pressure from players, coaches, and spectators, which can trigger psychosocial stressors. Environmental pressure and repeated verbal or physical aggression can potentially lead to emotional exhaustion and burnout, ultimately impacting the referee's psychological well-being and performance on the field. This study aims to analyze the relationship between psychosocial stressors, including environmental pressure and aggression, and burnout levels among football referees in Bandung. The research approach used was a quantitative correlational approach with a cross-sectional design. The results showed that environmental pressure had a significant positive relationship with emotional exhaustion (ρ= 0.666; p < 0.01) and cynicism (ρ= 0.400; p < 0.01). In addition, aggression is also significantly related to emotional exhaustion (ρ= 0.388; p < 0.01), but was not related to professional efficacy (ρ= 0.062; p = 0.671). These findings indicate that the higher the social pressure and aggression experienced, the greater the likelihood of referees experiencing burnout, especially in the emotional dimension. Therefore, psychological counseling programs, stress management training, and ongoing social support are needed for referees to maintain their mental well-being and professionalism.